Research Trends in Studies on Lifelong Learning: A Bibliometric Analysis with Visual Mapping Technique (2016-2020) - Duygu Gür Erdoğan (Sakarya University Journal of Education)
This study aims to use the bibliometric analysis method to examine the scientific articles published in the last five years (2016-2020) in the field of “lifelong learning” and to visualize the obtained data with the visual mapping technique. The data set consists of 779 educational research articles that are indexed in the “Web of Science” database and that contain the terms of “lifelong learning" or “lifelong education” in their abstract section. These articles were examined in terms of occurrence and co-occurrence of keywords, distribution of keywords by years, citations, co-citations, and publishing journals. VOSviewer software (1.6.9) was used for analysis, and data were visualized with mapping technique. Thus, it was aimed to view the major studies in the relevant field and to analyze the relations among them. It has been determined that the USA has the greatest number of articles on lifelong learning and that the International Journal of Lifelong Education has the greatest number of published articles. Furthermore, it has been found that lifelong learning is generally associated with keywords such as “Higher Education” and “Adult Education,” but there has also been an increase in recent years in the use of keywords such as “self-directed learning,” “collaborative learning,” “sustainable development goals,” “literacy,” “continuing professional development,” and “mobile learning.”